2019
DOI: 10.1155/2019/7954921
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Use of EGFR Mutation Analysis in Cell-Free DNA as a Follow-Up Biomarker during Different Treatment Lines in Non-Small-Cell Lung Cancer Patients

Abstract: Epidermal growth factor receptor (EGFR) mutational testing in advanced non-small-cell lung cancer (NSCLC) is usually performed in tumor tissue, although cfDNA (cell-free DNA) could be an alternative. We evaluated EGFR mutations in cfDNA as a complementary tool in patients, who had already known EGFR mutations in tumor tissue and were treated with either EGFR-tyrosine kinase inhibitors (TKIs) or chemotherapy. We obtained plasma samples from 21 advanced NSCLC patients with known EGFR tumor mutations, before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…Recently, Macias et al. showed that SQI decreased during the treatment response and increased during disease progression 33 . Presently, two plasma samples (sample ID S5 and S69) were analyzed during treatment in one patient.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, Macias et al. showed that SQI decreased during the treatment response and increased during disease progression 33 . Presently, two plasma samples (sample ID S5 and S69) were analyzed during treatment in one patient.…”
Section: Discussionmentioning
confidence: 91%
“…Two of the most important advancements in personalized medicine, especially in the field of lung cancer, include the use of cfDNA as a diagnostic and prognostic biomarker and next-generation sequencing (NGS) for the mutational analysis of lung tumors. For instance, EGFR and ALK have been identified as key biomarkers in lung cancer, and molecular tests for EGFR and ALK have become common in lung cancer treatment [24] . Circulating DNA as a biomarker is easily accessible, reliable, and reproducible and reduces the suffering and cost to society associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is more remarkable when using silica-gel columns as small DNA fragments (<100 bp) are loosed during isolation. The use of an isolation kit that captures all DNA fragments is of importance for the reliability of all downstream experiments, espe¬cially when the small DNA fractions (<100 bp) are considered the most informative as they rep¬resent characteristic qualitative changes in the primary tumor such as mutations [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exosome analysis could help in the screening and early detection of lung cancer, when patients have better prognosis [113,124], and some clinical trials are already addressing this issue (www.clinicaltrials.gov). However, exosome analysis has not been included in clinical guides yet, contrary to ctDNA where there are already clinical indications for its use as biomarker in lung cancer and some commercial kits are already available for mutations' assessment [8,155]. One of the reasons is the lack of standardized protocols for exosome isolation and analysis, which impairs the implementation of their analysis in a routine clinical laboratory.…”
Section: Discussionmentioning
confidence: 99%